Analysis of Digital Marketing Determinants on Customer Loyalty with Customer Satisfaction, Online Promotion and Customer Experience as Mediation Variables - Maria Assumpta Wikantari (International Journal of Economics Development Research (IJEDR), 2023)
The study's objective is to examine how digital marketing affects customer loyalty, using customer happiness, online advertising, and customer experience as mediating factors for Jakartan Ice Cream Mixue consumers. One hundred randomly selected Ice Cream Mixue customers in Jakarta served as the study's sample. After data processing using SEM Amos 25, research findings indicate that: (1) Digital marketing has no influence on online promotion, but has a favorable and significant impact on customer satisfaction and the whole Ice Cream Mixue experience for customers in Jakarta. (2) The online and customer experience, along with customer happiness, have a noteworthy and favorable impact on the customer loyalty of Ice Cream Mixue patrons in Jakarta. It is allowed for digital marketing to have an indirect impact on customer loyalty through improving customer satisfaction among Ice Cream Mixue customers in Jakarta. (4) It is disputed that online advertising serves as a mediating variable in the indirect impact of digital marketing on the customer loyalty of Ice Cream Mixue customers in Jakarta. (5) It is rejected that customer experience serves as a mediating variable in the indirect impact of digital marketing on the customer loyalty of Ice Cream Mixue customers in Jakarta.